Renewable energy and energy efficiency: An exploratory study in EU countries - Maria Basílio (Sustainable Futures)
Promoting energy efficiency and renewable energy adoption is a global priority, especially within the European Union (EU). This study evaluates the energy efficiency and renewable energy performance of 27 EU countries from 2015 to 2022. Using Data Envelopment Analysis (DEA), energy efficiency is assessed with three inputs—gross capital formation per capita, labor force, and energy consumption per capita—and two outputs—GDP per capita and GHG emissions. Under constant returns to scale, smaller EU members like Luxembourg, Malta, Ireland, and Cyprus perform best. Under variable returns to scale, newer Eastern EU members such as Bulgaria, Croatia, and Romania also rank highly. Fractional response models, bias-corrected via bootstrap techniques, identify key determinants of energy efficiency and renewable energy share. Energy efficiency is significantly influenced by energy prices, energy intensity, renewable energy share, R&D, and patents, with economic recessions positively impacting efficiency. For renewable energy adoption, critical factors include energy prices, government environmental spending, patents, and tertiary education levels.